Multi-event analysis of the westerly Greenland tip jet based upon 45 winters in ERA-40 - Våge, Kjetil; Spengler, Thomas; Davies, Huw C.; Pickart, Robert S. (Quarterly Journal of the Royal Meteorological Society, 2009)
ISSN:0035-9009 ISSN:1477-870X